Use of Lactobacillus paracasei strain for zearalenone binding and metabolization. (15th July 2020) - Złoch, Michał; Rogowska, Agnieszka; Pomastowski, Paweł; Railean-Plugaru, Viorica; Walczak-Skierska, Justyna; Rudnicka, Joanna; Buszewski, Bogusław
Abstract: The study investigated the zearalenone (ZEA) neutralization process as a consequence of metabolization and binding process by the probiotic bacterial strain Lactobacillus paracasei using high performance liquid chromatography (HPLC). In order to determine the nature of the binding process the kinetic and spectroscopic approach were used. Moreover, the influence of ZEA on L. paracasei metabolism was examined by the determination of the proteome profile of cells and the profile of volatile compounds (VOCs) produced by bacteria cells. For this purpose the Matrix-Assisted Laser Desorption/Ionization-Time of Flight mass spectrometry (MALDI-TOF MS) and headspace solid-phase microextraction coupled to gas chromatography/mass spectrometry (HS-SPME/GC-MS) techniques were used. The obtained results indicate that in the mechanism of ZEA neutralization both – metabolization/biotransformation and binding/biosorption processes are involved. Furthermore, the biotransformation of ZEA to both α- and β-ZOL with a predominance of β-ZOL by lactic acid bacteria strain was recorded. The results suggest that the tested microorganism can be used as a potential detoxification agent for grain and feed. Graphical abstract: Image 1 Highlights: L. paracasei effectively neutralize the zearalenone by both biosorption mechanism and metabolization to less toxic form.- Zearalenone has a significant impact on metabolism and viability of L. paracasei. Zearalenone has a significant impact on metabolism and viability of L. paracasei . L. paracasei cells adopt to the presence of ZEA by progressive shift in proteins composition within 48 h of incubation.